A Survey Paper of Study about Big Data - Choudhry, Pooja; Upadhyay, Shruti; Patel, Rakesh; Singh, Prateek Kumar (International Journal For Research In Advanced Computer Science And Engineering, 2016)
Big data is the term for data sets so large and complicated that it becomes difficult to process using traditional data management tools or processing applications. In this paper there is a information about Big Data, characteristics , structure , Big Data Analytics , application of analytics and benefits of big data. This paper also revels the recent progress on big data.